MEWFM 2022
DOI: 10.5742/mewfm.2022.952597
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Effect on Dietary Supplements’ Consumption, Prophetic Medicine Practices and Herbs Use in Saudi Arabia

Abstract: Background: The COVID-19 pandemic influenced dietary supplements’ (DS) consumption and practices of traditional medicine. Aims: This cross-sectional study aimed to compare dietary supplements, Prophetic medicine (PM) and herbal/plants (H/P) use among adults in Saudi Arabia before and during the COVID-19 pandemic. Method: 1351 individuals participated in the study via an online survey shared on social media platforms between December 11th, 2021, and March 1st, 2022. The survey tool included 31 questions about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This was consistent with previous studies conducted Saudi Arabia, that found a significant increase in DSs consumption among adult population during the Pandemic time. 8 DSs are used by many health professionals, including dietitians, physicians, and pharmacists. 8 and medical students were no exception.…”
Section: Perception Of Participants Regarding the Use Of Dss For Trea...mentioning
confidence: 99%
See 2 more Smart Citations
“…This was consistent with previous studies conducted Saudi Arabia, that found a significant increase in DSs consumption among adult population during the Pandemic time. 8 DSs are used by many health professionals, including dietitians, physicians, and pharmacists. 8 and medical students were no exception.…”
Section: Perception Of Participants Regarding the Use Of Dss For Trea...mentioning
confidence: 99%
“…8 DSs are used by many health professionals, including dietitians, physicians, and pharmacists. 8 and medical students were no exception.…”
Section: Perception Of Participants Regarding the Use Of Dss For Trea...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Arab Emirates multivitamins (77.8%) were found to be the most commonly used FS during the COVID-19 pandemic [35]. In another study nerede?, it was determined that the most frequently used FS during the pandemic were vitamin C (87.6%), vitamin D (76.9%) and multivitamins (69.7%) [19]. Francis et al [36] found that 46.0% of adults used vitamin C, 10.8% used multivitamins and 8.6% used vitamin D supplements during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…DiscussionFood Supplements Use and Pandemic An optimal diet can help improve overall health, reduce the risk of disease, and reduce the rate of morbidity associated with COVID-19[18]. It has been shown that the use of FS has increased in different countries during the COVID-19 pandemic [8,[19][20][21][22]. FS use before and during the pandemic were 29.5% and 71.9% in Asia, 21.3% and 75.7% in USA, 30.8% and 68.7% in Europe, and 21.3% and 62.2% in Turkey, respectively,[23], In the United Arab Emirates 56.5% of adults used FS during the COVID-19 pandemic period; 53.8% of them started to use FS with the beginning of COVID-19 pandemic[24].…”
mentioning
confidence: 99%